2022
DOI: 10.3390/coatings12020122
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Thin 2D van der Waals Magnetic Materials: Fabrications, Structure, Magnetic Properties and Applications

Abstract: Two-dimensional (2D) van der Waals (vdW) magnetic materials are considered to be ideal candidates for the fabrication of spintronic devices because of their low dimensionality, allowing the quantization of electronic states and more degrees of freedom for device modulation. With the discovery of few-layer Cr2Ge2Te6 and monolayer CrI3 ferromagnets, the magnetism of 2D vdW materials is becoming a research focus in the fields of material science and physics. In theory, taking the Heisenberg model with finite-rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 225 publications
(291 reference statements)
0
7
0
Order By: Relevance
“…Despite the fair number of reviews already published on this topic as cited above, [ 12–33 ] we present an updated review motivated by the rapid pace of advancement in this field and a number of more recent and important new developments, ranging from new experimental methods to new or less reviewed properties (e.g., magnetic, superconducting, electrochemical) explored in strain engineering. In this review, we summarized and discussed recently reported new methods to induce strain, updated the latest developments on the modification of electrical, magnetic, and optical properties of 2D materials by strain engineering, and presented future perspectives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fair number of reviews already published on this topic as cited above, [ 12–33 ] we present an updated review motivated by the rapid pace of advancement in this field and a number of more recent and important new developments, ranging from new experimental methods to new or less reviewed properties (e.g., magnetic, superconducting, electrochemical) explored in strain engineering. In this review, we summarized and discussed recently reported new methods to induce strain, updated the latest developments on the modification of electrical, magnetic, and optical properties of 2D materials by strain engineering, and presented future perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Given the promising application of strain engineering of 2D materials, there have emerged increasing number of research studies and review papers on this topic. [ 12–33 ] For example, Guinea [ 29 ] reviewed strain engineering on the electronic properties of graphene. Bissett et al.…”
Section: Introductionmentioning
confidence: 99%
“…Reports of real‐space direct imaging of the magnetic domain structures in vdW ferromagnets have been limited, however, as many of the materials have a low Curie temperature ( T c ), weak magnetic moments, or are otherwise difficult to image because of compensated spin structures or sample volatility and degradation. [ 19 ] Direct imaging is especially important for emergent non‐trivial spin structures, such as skyrmions and merons, which have been reported in similar materials, namely Fe 3 GeTe 2 [ 20 ] and Fe 5 GeTe 2 , [ 21 ] because the relevant length scale of these features is often less than 100 nm. These materials display magnetic bubbles and Néel skyrmions which arise from an interfacial Dzyaloshinskii Moriya interaction (DMI) and can have a relatively high Curie temperature of 220 K. [ 20,22,23 ]…”
Section: Introductionmentioning
confidence: 99%
“…There is always a challenge to achieving 2D magnetism intrinsically, as most of the synthesized 2D materials are nonmagnetic. With the introduction of anisotropy or by doping incorporation or quantum confinement, magnetism can be induced in nonmagnetic 2D systems. However, such systems have limited practical applications as the enabled magnetism is generally not robust . In this regard, few MXenes, along with some monolayer magnets, for example, CrI 3 and VSe 2 , are becoming the research focus in the materials science community due to their inherent magnetic property.…”
Section: Introductionmentioning
confidence: 99%